Trying Home : The Rise and Fall of an Anarchist Utopia on Puget Sound - Wadland, Justin (Book collections on Project MUSE., 2014)
"The true story of an anarchist colony on a remote Puget Sound peninsula, Trying Home traces the history of Home, Washington, from its founding in 1896 to its dissolution amid bitter infighting in 1921. As a practical experiment in anarchism, Home offered its participants a rare degree of freedom and tolerance in the Gilded Age, but the community also became notorious to the outside world for its open rejection of contemporary values. Using a series of linked narratives, Trying Home reveals the stories of the iconoclastic individuals who lived in Home, among them Lois Waisbrooker, an advocate of women's rights and free love, who was arrested for her writings after the assassination of President McKinley; Jay Fox, editor of The Agitator, who defended his right to free speech all the way to the Supreme Court; and Donald Vose, a young man who grew up in Home and turned spy for a detective agency. Justin Wadland weaves his own discovery of Home--and his own reflections on the concept of home--into the story, setting the book apart from a conventional history. After discovering the newspapers published in the colony, Wadland ventures beyond the documents to explore the landscape, travelling by boat along the steamer route most visitors once took to the settlement. He visits Home to talk with people who live there now. Meticulously researched and engagingly written, Trying Home will fascinate scholars and general readers alike, especially those interested in the history of the Pacific Northwest, utopian communities, and anarchism"--